Implementing the PDCA Cycle for Social Media Integration in Education: A Multiple Case Study of Quality Management Practices - Asep Zenal Mutakin; Teti Ratnawulan Surtiati (Papanda Publisher, 2026)
The integration of social media in education presents paradoxical challenges, with platforms predominantly used for entertainment despite their pedagogical potential. This study examines how systematic quality management frameworks can optimize social media utilization to enhance student learning motivation. Employing a qualitative multiple case study design, this research investigated quality management practices at two Indonesian secondary schools (SMP Negeri 3 and 4 Pagelaran, Cianjur Regency). Data were collected through observations, semi-structured interviews with 40 participants (principals, teachers, students, parents), and documentary analysis. The PDCA (Plan-Do-Check-Act) cycle framework guided analysis using Miles and Huberman's interactive model. Findings revealed systematic implementation across planning, organization, implementation, and evaluation phases, though with varying effectiveness. Both schools demonstrated strategic planning with stakeholder involvement, clear organizational structures, diverse platform utilization (WhatsApp, YouTube, Google Classroom, Instagram), and iterative evaluation mechanisms. However, persistent challenges included digital literacy gaps, infrastructure limitations, teacher pedagogical anxieties, and assessment complexities. Student-initiated peer support networks and metacognitive development emerged as unexpected positive outcomes. Results confirm that structured quality management grounded in the PDCA cycle can transform social media into purposeful learning instruments when aligned with Self-Determination Theory principles. Success requires comprehensive institutional ecosystems addressing organizational, pedagogical, motivational, and socio-cultural dimensions simultaneously, with continuous capacity-building across all stakeholder groups.